Effectiveness of Video and Leaflet Educational Media on Postpartum Mothers’ Knowledge and Attitudes Toward Exclusive Breastfeeding: A Quasi-Experimental Study - Manjorang, Novita Andriani Br.; Sembiring, Ninsah Mandala Putri; Yun, Deby Cyntia; Hutasoit, Naomi; Heriani, Siska (Journal of Applied Nursing and Health, 2026)
Background: Exclusive breastfeeding (EBF) is essential to reduce infant morbidity and mortality, yet EBF coverage in Indonesia remains suboptimal, partly due to limited maternal knowledge and less supportive attitudes. Comparing educational media such as video and leaflets is important to identify effective and scalable approaches for postpartum breastfeeding counseling. To determine the effectiveness of video media and leaflet media in improving postpartum mothers’ knowledge and attitudes toward exclusive breastfeeding. Methods: This quasi-experimental two-group pretest–posttest study was reported in line with the TREND guideline for nonrandomized evaluations. Participants were recruited using purposive sampling from postpartum mothers and allocated into two nonrandomized intervention groups (video vs leaflet; 30 per group). Inclusion criteria were postpartum mothers ≤6 weeks, willing to participate, able to communicate in Bahasa Indonesia, and (for video group) having smartphone access to view the material; exclusion criteria included cognitive/psychological disorders or inability to complete the session. Knowledge and attitude were assessed using validated questionnaires before and immediately after a standardized 30-minute education session. Data were analyzed using SPSS version 25; within-group changes were tested with paired-samples t-tests, and effect sizes were calculated using Cohen’s d. Results: Both interventions significantly improved knowledge and attitude scores (p<0.001). In the video group, knowledge increased from 50.67±9.59 to 89.77±7.27 (Cohen’s d=3.93), and attitude increased from 48.53±10.23 to 85.37±5.56 (Cohen’s d=3.56). In the leaflet group, knowledge increased from 49.60±10.13 to 88.00±6.75 (Cohen’s d=3.89), and attitude increased from 48.17±10.29 to 85.53±6.25 (Cohen’s d=3.31). Conclusion: Video and leaflet education were both highly effective in improving postpartum mothers’ knowledge and attitudes toward EBF, with very large effect sizes in both groups; video showed a slightly larger effect on attitudes. Integrating video and leaflets into routine postpartum counseling may strengthen EBF promotion in primary care settings.